THE USE OF INFORMATION COMMUNICATION AND TECHNOLOGY (ICT) IN ENGLISH LANGUAGE LEARNING: A CASE STUDY AT ONE PUBLIC UNIVERSITY IN JAMBI - Haryanto, Eddy; Oktalia, Dwi (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2014)
This research is aimed to describe students’ perception toward the use of Information Communication and Technology (ICT) in language learning. The objective of the study is to know students’ perception toward the use of ICT in language learning and to know the problem that they encountered during the use of ICT. The design of this research was survey method. The subject of this research was sixth semester students’ of English department Jambi University. A questionnaire was main instrument to gather the data. The questionnaire consists of items regarding the educational resources of respondents, their reasons for using ICT, the use of ICT in learning process and the problems that they encountered. The result of the study showed that ICT is useful for students. Using ICT can help students easier in accessing information they need which can bring positive effect for students, but this should supported by sufficient ICT equipment and ability to determine information which they search for in order to give better performance since the number one problem faced by students come from two numbers which are, few staff using ICT and information from ICT always change. It is recommended for lecturer to involve ICT services during the teaching and learning process more often and giving guidance to students to determine the appropriate material for their needs. Keyword: Information communication and technology, English language learning